Magneto-Dielectric Synergy and Multiscale Hierarchical Structure Design Enable Flexible Multipurpose Microwave Absorption and Infrared Stealth Compatibility - Li, Chen; Liang, Leilei; Zhang, Baoshan; Yang, Yi; Ji, Guangbin (Nano-Micro Letters, 2024)
Developing advanced stealth devices to cope with radar-infrared (IR) fusion detection and diverse application scenarios is increasingly demanded, which faces significant challenges due to conflicting microwave and IR cloaking mechanisms and functional integration limitations. Here, we propose a multiscale hierarchical structure design, integrating wrinkled MXene IR shielding layer and flexible Fe3O4@C/PDMS microwave absorption layer. The top wrinkled MXene layer induces the intensive diffuse reflection effect, shielding IR radiation signals while allowing microwave to pass through. Meanwhile, the permeable microwaves are assimilated into the bottom Fe3O4@C/PDMS layer via strong magneto-electric synergy. Through theoretical and experimental optimization, the assembled stealth devices realize a near-perfect stealth capability in both X-band (8–12 GHz) and long-wave infrared (8–14 µm) wavelength ranges. Specifically, it delivers a radar cross-section reduction of − 20 dB m2, a large apparent temperature modulation range (ΔT = 70 °C), and a low average IR emissivity of 0.35. Additionally, the optimal device demonstrates exceptional curved surface conformability, self-cleaning capability (contact angle ≈ 129°), and abrasion resistance (recovery time ≈ 5 s). This design strategy promotes the development of multispectral stealth technology and reinforces its applicability and durability in complex and hostile environments. Highlights: 1 A multiscale hierarchical structure design, integrating wrinkled MXene radar-infrared shielding layer and flexible Fe3O4@C/PDMS microwave absorption layer 2 The assembled stealth devices realize a near-perfect stealth capability in both X-band (8-12 GHz) and long-wave infrared (8-14 µm) wavelength ranges. 3 The optimal device demonstrates exceptional curved surface conformability, self-cleaning capability (contact angle ≈ 129°), and abrasion resistance (recovery time ≈ 5 s).